The Problem of Recurrent Injuries in Collegiate Track and Field - Chris Hopkins; Samantha Kanny; Catherine Headley (North American Sports Medicine Institute, 2022)
# Background As with most sports, participating in Track and Field (T&F) has inherent injury risks and a previous injury often predisposes athletes to a greater future injury risk. However, the frequency and burden of recurrent injuries in collegiate T&F have not been closely examined. # Purpose The purpose of this study was to describe the frequency and burden of recurrent injuries in collegiate T&F and compare differences in the time loss associated with initial and recurrent injuries by sex and T&F discipline. # Study Design Descriptive Epidemiology Study # Methods Data from the NCAA Injury Surveillance Program were analyzed to describe the frequency and burden of recurrent injuries in collegiate T&F between 2009 and 2014. Comparisons of recurrent injury proportions by T&F discipline were made using Injury Proportion Ratios (IPR) and injury-associated time loss comparisons by injury type and sex were made using Negative Binomial Regression. # Results Four hundred and seventy-four injuries were reported, 13.1% of which were classified as recurrent injuries. T&F athletes who competed in jumps experienced a lower proportion of recurrent injuries (6.1%) than runners (14.6%) and throwers (19.2%) (Recurrent IPR 0.40, 95% CI 0.18-0.88, p\<0.05). When controlling for sex and injury diagnosis, T&F athletes experienced 50% greater time loss from sport following a recurrent injury than an initial injury (95% CI 17%-107%, p\<0.01). # Conclusions Recurrent injuries in T&F athletes account for greater time loss than initial injuries, despite sex or injury diagnosis. The current study indicates a need for further research to assess factors contributing to time loss. # Level of Evidence Level 3